366. SURGERY VERSUS NON-SURGICAL TREATMENT FOR THORACIC ESOPHAGEAL CANCER IN PATIENTS OLDER THAN 70 YEARS: A RETROSPECTIVE ANALYSIS OF 749 CASES. (24th September 2022) - Li, Kexun; Leng, Xue Feng; Du, Kunyi; Liu, Kun; He, Wenwu; Wang, Qifeng; Luo, Xi; Wang, Chenghao; Wang, Kangning; Liu, Guangyuan; Wei, Xing; Li, Haojun; et al.
Abstract: The highest incidence of esophageal cancer is in East Asia, but as for advanced age people, there are also many non-tumor factors affecting overall survival (OS), such as cardiovascular and cerebrovascular diseases. Our purpose is to determine whether the older patients after esophagectomy had better OS than those treated with non-surgical treatment. Data were obtained from the Sichuan Cancer Hospital & Institute Esophageal Cancer Case Management Database (SCH-ECCM Database) and Department of Radiation Oncology Database. We retrospective analyzed esophageal cancer patients older than 70 years who underwent esophagectomy or radiotherapy/chemotherapy from Jan. 2009 to Dec. 2017. The patients were divided into two groups: surgery group (S group), and non-surgery group (NS group). Outcome measures depend on OS. After 60.6 months of median follow-up time, 749 patients were included. 532 of 749 patients (71.0%) underwent surgery, 217 of 749 patients (39.0%) underwent non-surgical treatment including radiotherapy and/or chemotherapy. In the S group, the median OS of was 39.7 months (95% CI 33.7–45.7), while the NS group was only 24.0 months (95% CI 19.6–28.4). The OS at 1, 3, and 5 years were 84%, 52%, and 39% in the S group, respectively. In the NS group, the OS rates at 1, 3, and 5 years were 72%, 32%, and 29%, respectively (HR 0.69, 95% CI 0.561–0.846, P<0.0001). Esophageal cancer patients older than 70 years who underwent esophagectomy had significantly better OS than those who underwent non-surgical treatment based on radiotherapy and/or chemotherapy.